Reconstruction of Technology Development "Energy Independent Village Based on Vortex Hydro Power Plant (PLTHV)" through the Application of New and Renewable Energy Technology - Muhammad Hasan Basri; Ilmirrizki Imaduddin; Bachtera Indarto; Dicky Mas'udi Soleh; Moh. Fathul Qorib; Muhammad Andriansah (Unram Journal of Community Service, 2025)
This community service program, funded by the Ministry of Education, Culture, Research, and Technology in 2025, was implemented in Duren Village, Probolinggo Regency, through collaboration between Nurul Jadid University (UNUJA) and the Institut Teknologi Sepuluh Nopember (ITS). The project aimed to develop an energy self-sufficient village by reconstructing the Hydro Vortex Power Plant (PLTHV) using renewable energy technologies such as the Electronic Voltage Stabilizer (EVS) and Power Circuit Breaker (PMT). The activities included field surveys, training, installation, testing, and mentoring. The reconstructed PLTHV successfully increased output capacity from 130 watts to 217 watts, improving energy efficiency and stability while reducing household electricity costs by approximately IDR 200,000 per month. Beyond technical improvements, the program enhanced community knowledge, encouraged active participation in managing renewable energy systems, and provided experiential learning opportunities for students. This initiative supports Sustainable Development Goal 7 (Affordable and Clean Energy) and demonstrates the potential of community-based renewable energy projects to reduce fossil fuel dependency and strengthen rural energy resilience.